Balkanization of the West : the Confluence of Postmodernism and Postcommunism. - Mestrovic, Stjepan (Routledge, 1994)
This book takes the lid off the confused Western response to the Balkan war. The author raises a series of timely and acute questions about the future of postmodernism and postcommunism.